The Role of Educational Philosophy in Student Character Formation for The Digital Age: A Systematic Literature Review - Yeni Susanti; Devi Sylvianica (Yayasan Sembilan Pemuda Indonesia, 2026)
The accelerating integration of digital technologies in education has reshaped learning environments while introducing complex challenges related to ethics, social behavior, and student character development. This study systematically examines how educational philosophy informs and supports character formation in the digital age. Employing a Systematic Literature Review (SLR) approach, 17 peer-reviewed studies published between 2020 and 2024 were identified through Scopus, screened using PRISMA procedures, and analyzed through thematic synthesis. The review identifies three major themes: (1) Foundational philosophical perspectives particularly perennialism, essentialism, and virtue ethics remain central in cultivating enduring moral values, discipline, and integrity; (2) Progressive and constructivist approaches offer dynamic pathways for fostering ethical reasoning, socio-emotional skills, multicultural understanding, and collaborative digital citizenship through dialogic and inquiry based learning; and (3) a persistent digital-philosophical gap, wherein rapid technological adoption in schools is not yet accompanied by adequate philosophical grounding, teacher preparedness, or ethical digital frameworks. The study contributes a synthesized conceptual lens linking philosophy, character education, and digital learning, demonstrating that effective digital moral formation requires harmonizing classical virtues with reflective, technologically responsive pedagogies. This review urges policymakers and educators to embed philosophical literacy and ethical reasoning into digital education reforms, teacher professional development, and curriculum design. Future research should empirically validate integrated philosophical-digital character models across diverse educational contexts.